Development of Powtoon Learning Media for Student Learning Activities in Theme 2 Clean Air For Health Class V SDN 064954 Medan Amplas - Amaliya, Putri; Landong, Ahmad (Widyagogik, 2023)
This study aims to: (1) develop Powtoon learning media for student learning activities on theme 2 clean air for health for grade V SD, (2) determine the feasibility of developing the Powtoon application in SD thematic learning. This research is a type of Research and Development (RD) research with the ADDIE model which includes five steps including: analysis, design, development, implementation, evaluation. The subjects in this study were media expert validators, education practitioners, material experts, namely fifth grade teachers and fifth grade elementary school students. The research instruments used in data collection were questionnaires, observation, and documentation. The results of this study indicate that Powtoon learning media in Thematic Learning Theme 2 Clean Air for Health Class V SD "Very Eligible" with details of the eligibility percentage given by Media Experts in sub-theme 1 of 71.6% in the "Decent" category, media sub-theme 2 86.6% in the "Very Eligible" category, 88.3% in subtheme 3 media in the "Very Eligible" category. Material experts on media sub-theme 1 are 76% in the category "Appropriate", sub-theme 2 are 88% in the "Very Eligible" category, sub-theme 3 is 90% in the "Very Eligible" category. In Education Practitioners, the media subtheme 1 is 90% with the category "Very Eligible", subtheme 2 is 90% with the category "Very Eligible", subtheme 3 is 90% with the category "Very Eligible", Individual Trials are 90.8% with category "Very Feasible" and Student Learning Activities by 80% with the category "Very Feasible". Therefore it can be concluded that the Powtoon learning media for student learning activities on theme 2 clean air for the health of class V SDN 064954 Medan Amplas is "very appropriate" to be used with students during the learning process.